2013
DOI: 10.3109/10582452.2013.827289
|View full text |Cite
|
Sign up to set email alerts
|

The Relaxation Response Resiliency Enhancement Program in the Management of Chronic Refractory Temporomandibular Joint Disorder: Results from a Pilot Study

Abstract: Objectives This is an open-pilot study to evaluate the feasibility, acceptability and efficacy of a pain-specific version of an established mind–body medicine program, the Relaxation Response [RR] Resiliency Program [R3P], in patients with chronic temporomandibular disorder [TMD]. Methods Male and female with at least a six-month history of pain involving the masticatory muscles were sought in the Orofacial Pain Centers of the Massachusetts General Hospital [MGH] or through an advertisement sent to MGH emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…for PTSD [13,14,15,16], catastrophic thinking and pain anxiety [17][18][19], depression [20][21][22], perceived disability [23] and pain intensity and overall medical symptom reduction [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…for PTSD [13,14,15,16], catastrophic thinking and pain anxiety [17][18][19], depression [20][21][22], perceived disability [23] and pain intensity and overall medical symptom reduction [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Our 3RP-NF intervention was adapted from the original 3RP program, designed to elicit the "relaxation response" (RR), a state of calm awareness, through relaxation and mindfulness skills. Like other mindfulness-based interventions (Marino et al, 2021;Sanada et al, 2017), the 3RP program has demonstrated ability to improve health indicators and well-being for a number of health conditions but required adaptation to suit the unique needs of individuals with NF (Bhasin et al, 2013;Denninger et al, 2014;Kuo et al, 2015;Vranceanu et al, 2013Vranceanu et al, , 2014. In the first fully powered single-blinded randomized controlled trial of a psychosocial NF intervention, 3RP-NF demonstrated sustained improvements in QoL compared with a dose-matched health education control (the Health Enhancement Program for NF, HEP-NF; Vranceanu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The TMD non-surgical approach consists of a recognized health care protocol set that includes; a) cognitive-behavioral therapy aiming for relaxation and habit-breaking (36,37) , b) pharmacological approach (using Anti-inflammatories and muscle relaxants or anti-depressants in severe cases) (38,39) , c) modalities of physical therapy (electro-physical, massage, or physical exercise) (40,41) , d) Wearing an oral appliance (OAs) or an occlusal orthotic (splint) (42) , e) a combination of these approaches.…”
Section: Introductionmentioning
confidence: 99%